2021
DOI: 10.1111/pedi.13299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of HbA1c and glucose management indicator discordance in a population of children and adolescents with type 1 diabetes

Abstract: Background Glucose management indicator (GMI) is a useful metric for the clinical management of diabetic patients using continuous glucose monitoring (CGM). In adults, a marked discordance between HbA1c and GMI has been reported. To date, no studies have evaluated this discordance in children/adolescents with type 1 diabetes (T1D). Methods HbA1c and real‐life CGM data of the 12 weeks preceding HbA1c measurement were collected from 805 children/adolescents. The absolute difference between HbA1c and GMI was calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 7 publications
2
29
0
Order By: Relevance
“…When a laboratory HbA1c value is known, it becomes possible to calculate an estimated value for average glucose, using a weighted least‐squares regression of Mean Glucose on HbA1c 18 . Many studies have observed that these two variables are linearly related 3,4,17‐20 . Likewise, one can obtain an estimate of HbA1c from a measured Mean Glucose value, using an unweighted least squares linear regression of observed HbA1c on Mean Glucose 19,20 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When a laboratory HbA1c value is known, it becomes possible to calculate an estimated value for average glucose, using a weighted least‐squares regression of Mean Glucose on HbA1c 18 . Many studies have observed that these two variables are linearly related 3,4,17‐20 . Likewise, one can obtain an estimate of HbA1c from a measured Mean Glucose value, using an unweighted least squares linear regression of observed HbA1c on Mean Glucose 19,20 .…”
Section: Resultsmentioning
confidence: 99%
“…The principal method used in the present study was to compare Spearman correlation coefficients among HbA1c , Mean Glucose , %TIR , and %TAR for T1D, 14,16 and Pearson correlation coefficients among Mean Glucose , %TIR , and %TAR for T2D 15 . We did not examine correlations with proportion of time below range, which is very weakly correlated with the other four CGM metrics 4 . Our goal was to identify the metrics most closely correlated with HbA1c and Mean Glucose , based on the premise that metrics with the highest correlation with Mean Glucose would be associated with the long‐term complications of diabetes 8 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the quarterly HbA1c is not always adequately reflected by software GMI, mean sensor glucose, TiR, and TbR, and so cannot be simply replaced by software measures in all patients [36] . For this reason, from our perspective, before starting primarily video consultation-based care, it is advisable to compare an HbA1c value from the outpatient clinic with the corresponding GMI from a 4-week evaluation and check whether the GMI deviates clinically significantly, i.e., more than 0.5%, in case of incorrectly low calibrated sensors, for example.…”
Section: Discussionmentioning
confidence: 99%